DYNAMICS OF INDICATORS OF VEGETATIVE REGULATION OF HEART RHYTHM OF QUALIFIED BOXERS UNDER THE INFLUENCE OF A COMPLEX OF EXTRA-TRAINING MEANS OF STIMULATING DIRECTION - Rybachok, R. O.; Protsenko, A. A.; Sukhanova, H. P. (Rehabilitation and Recreation, 2023)
One of the factors for improving sports activity in boxing is the integration of extra-training means, taking into account the specifics of its structural formations. The use of stimulating extra-training means will optimize the pre-start condition of boxers and increase the effectiveness of competitive activity. The purpose of the study was to determine the features of the effect of a complex of extra-training effects on the autonomic regulation of the heart rate of qualified boxers, taking into account the individual characteristics of the body. The experimental complex includes massage techniques for tense muscles and special physical exercises with a partner. Research results. There are significant differences in the indicators of heart rate variability among qualified boxers after different warm-ups. The results of the study indicate a greater activity of the parasympathetic division of the autonomic nervous system after the application of the experimental complex. The use of a complex of extra-training effects optimizes the functional state of athletes by increasing the efficiency of functional systems, which indicates an increase in the degree of recovery of the body. Preservation of the activity of the sympathetic division of the autonomic nervous system at a certain level maintains high possibilities for activating body functions in response to subsequent physical exertion. Conclusions. The analysis of the data obtained showed significant differences in the body reactions of the boxers of the two groups to the experimental extra-training effects. This will make it possible to make a correction in the tactics of conducting a sports fight. The implementation of the pre-start complex of extra-training influences in the sports training of qualified boxers will make it possible to influence the activation of the body’s functional systems, achieve a greater depth of training load and increase the effectiveness of the competitive activity.